Feasibility Test of Guided Inquiry Model Learning Devices Assisted by 3D Experimental Media on Sound Wave Material - Yulina Hasnaini; Aris Doyan; Sutrio (Postgraduate, University of Mataram, 2024)
This research aims to determine the feasibility of a guided inquiry model physics learning device assisted by 3D experimental media on sound wave material. The type of research used is research and development with a 4D research model. The products developed are syllabi, learning implementation plans (RPP), student worksheets (LKPD), and test instruments. Data collection was carried out through validation sheets of learning tools by expert validators and practitioners, and reliability analysis using percentage of agreement (PA). The validation results obtained show that the syllabus, RPP, LKPD and test instruments with an overall average of 86.29% are in very valid criteria and the results of the reliability analysis show that the overall average value of the learning tools is 93.32% in reliable criteria. Based on this, it can be concluded that the guided inquiry learning tool assisted by 3D experimental media is suitable for application in learning sound waves in the classroom.